Transthyretin amyloid cardiomyopathy: a 2-year single-centre experience. (3rd October 2022) - Rocha, B; Amador, R; Maltes, S; Marques, M; Oliveira, C; Lopes, P; Cunha, G; Paiva, M; Strong, C; Abreu, F; Pintao, S; Aguiar, C; et al.
Abstract: Background: Transthyretin Amyloid Cardiomyopathy (ATTR-CM) is an under-diagnosed condition often presenting with Heart Failure (HF). We aimed to assess a cohort of patients with ATTR-CM and HF, focusing on the centre strategies to identify new cases, prognosticate and tailor treatment. Methods: We conducted an all-comers single-centre prospective registry of consecutive patients with HF due to ATTR-CM followed in our centre from November 2019 to 2021. As per site protocol, diagnosis is established according to the algorithm by Gilmore et al. and all patients are assessed in our HF outpatient clinic at least twice yearly with systematic electronic chart data collection. We evaluated disease-modifying treatment and compliance with the current European Guidelines and CHAD-STOP management. A summary of this program is presented in the central figure. Results: Overall, 60 patients were included (mean age 83±7 years; 80% male). ATTR-CM was confirmed by the non-invasive algorithm in all but 8 patients, in whom endomyocardial biopsy was positive. Of those undergoing genetic testing (n=30), 7 (23%) presented with the hereditary form of ATTR-CM (4 Val50Met and 3 Val142Ile mutations). The initial presentation was most often HF (n=43), atrial fibrillation (n=9), or "incidental" myocardial uptake on 99mTc-HMDP bone scintigraphy (grade 2) performed for cancer staging (n=5). Beta-blockers were reduced or stopped in 40 (67%) patients, all of whom improved in NYHA class and/or NT-proBNP (>30% reduction) at 1–3 months. Tafamidis 61mg was started in 22 patients and 15 more currently await approval. Those initiated on or referred to tafamidis 61mg (n=37) had less severe HF, as per NYHA (class I-II – 94 vs. 50%, p=0.033) and performance status (e.g. Karnofsky score 80–100 – 79 vs. 21%, p=0.010). Of those already on tafamidis (n=22), NYHA class remained stable or improved in all but 1 patient. In the year following vs. preceding treatment there was 2 vs. 3 total HF hospitalizations. No drug-related severe adverse events were reported. Over a 2-year follow-up, 14 (23.3%) patients died, of whom 1 was on tafamidis (compassionate use for 19 months). Conclusions: ATTR-CM recognition is improving in our dedicated rare disease program, possibly due to the implementation of several alert pathways. The identification of the disease at an earlier stage allows targeted treatment, compliant with the recommendations. Nonetheless, the rarity of this disease and the required expertise for its optimal management argues in favour of a national strategic plan based on referral centres for ATTR-CM. Funding Acknowledgement: Type of funding sources: None.